Effect of Stretching Exercise to Increase Joint Range of Motion and Functional Ability in Post-Burn Shoulder Contracture Patients: A Case Report - Raga Geriana Novita Dewi; Suryo Saputra Perdana; Nilam Nur Hamidah (Ahmar Metastasis Health Journal, 2023)
Burns are tissue damage or loss caused by contact with high temperatures, such as heat, radiation, electricity, and chemicals. Causes damage to the epidermis and underlying soft tissue, bone, and muscle, placing burn victims at risk for contractures and joint deformities. Upper extremity function is critical to the performance of activities of daily living. Interventions such as surgery, pharmacological therapy, and nutritional support are important in aiding recovery and improving clinical outcomes after severe burns. The aimed to determine the effect of stretching exercises on increasing range of motion and functional ability in post-burn shoulder contracture. This study used the case study method which was conducted on post-shoulder contracture burn patients at Central General Hospital Dr. I.G.N.G Ngoerah Bali in February 2023. Pain measurements were taken using the Numeric Rating Scale (NRS). Measurement of muscle strength using Manual Muscle Testing (MMT). Goniometer to measure the Range of Joint Motion (ROM). Shoulder Pain and Disability Index (SPADI) to measure functional ability. SPADI is a quality of life questionnaire consisting of 13 items to evaluate 5 items for pain and 8 items for impairment. After 3 times of physiotherapy, the results showed a decrease in silent pain at T0 = 2 to T3 = 1. Tenderness at T0 = 4 to T3 = 2. Movement pain T0 = 5 to T3 = 3. Increased muscle strength T0 value 2, that is not full ROM to T3 value 3, namely full ROM and can fight gravity. Increased range of motion in active and passive flexion, extension, abduction, adduction, horizontal, abduction and horizontal adduction, internal and external rotation. The increase in the functional ability of SPADI T0 = 53% then decreased to T3 = 35%. There is a significant decrease in the measurement of functional ability using SPADI, which means the patient's functional ability is increasing. The conclusion is stretching exercises are effective for increasing the range of motion and functional ability of patients with post-burn shoulder contractures. Therefore, stretching exercises should be used to provide proper burn care to patients in hospitals and burn centers.